2000
DOI: 10.1034/j.1399-3003.2000.16b18.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrated proteins in bronchoalveolar lavage fluid of patients at risk of ventilator-associated bronchopneumonia

Abstract: The study was designed to identify markers of oxidative injury, related to the nitric oxide derived cascade, in bronchoalveolar lavage (BAL) fluid from intensive care patients suspected of ventilator-associated pneumonia (VAP) and/or acute respiratory distress syndrome (ARDS).Thirty-eight patients developing VAP and/or ARDS (VAP/ARDS group) were compared to 20 ventilated patients without VAP/ARDS (control group). Myeloperoxidase (MPO) and elastase, taken as markers of neutrophil activation were measured by enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…We previously demonstrated that an oxidant activity is present in BAL fluid from ventilated patients and that this BAL fluid is cytotoxic to normal alveolar cells in culture [11]. In the present study, we demonstrate that these BAL fluids can induce activation of the transcription factor NF-κB in alveolar cells.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…We previously demonstrated that an oxidant activity is present in BAL fluid from ventilated patients and that this BAL fluid is cytotoxic to normal alveolar cells in culture [11]. In the present study, we demonstrate that these BAL fluids can induce activation of the transcription factor NF-κB in alveolar cells.…”
Section: Introductionmentioning
confidence: 48%
“…As described previously [11], the occurrence of nitrated proteins in BAL fluid was quantified using a competitive nitrotyrosine ELISA kit (TCS Cell Works). The lower limit of detection was 0.1 µg\ml nitrated BSA equivalents.…”
Section: Measurement Of Nitrated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were similar to those of Nowak et al [10] on lipid peroxidation products and blood neutrophils. On the other hand, TAS change was correlated with total WBC, suggesting that other sources of ROS may be involved in peripheral blood oxidant/antioxidant imbalance, except neutrophils, such as monocytes or even lung alveolar macrophages [18, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, increased ROS production was found in bronchoalveolar lavage fluid from these patients, especially in those that were severely immunocompromised [18]. This oxidative response was mainly due to neutrophil recruitment and activation, as a positive correlation was found with the percentage of neutrophils and release of myeloperoxidase, the main enzyme for their respiratory burst and antibacterial activity [18, 19]. Increased markers of oxidant injury, such as nitrated proteins, have been found in bronchoalveolar lavage fluid in patients with ventilator-associated pneumonia.…”
Section: Discussionmentioning
confidence: 99%